Concise Review: Stem/Progenitor Cell Proteoglycans Decorated with 7-D-4, 4-C-3, and 3-B-3(-) Chondroitin Sulfate Motifs Are Morphogenetic Markers of Tissue Development. (31st July 2018) - Hayes, Anthony J.; Smith, Susan M.; Caterson, Bruce; Melrose, James
Abstract : This study reviewed the occurrence of chondroitin sulfate (CS) motifs 4-C-3, 7-D-4, and 3-B-3(-), which are expressed by progenitor cells in tissues undergoing morphogenesis. These motifs have a transient early expression pattern during tissue development and also appear in mature tissues during pathological remodeling and attempted repair processes by activated adult stem cells. The CS motifs are information and recognition modules, which may regulate cellular behavior and delineate stem cell niches in developmental tissues. One of the difficulties in determining the precise role of stem cells in tissue development and repair processes is their short engraftment period and the lack of specific markers, which differentiate the activated stem cell lineages from the resident cells. The CS sulfation motifs 7-D-4, 4-C-3, and 3-B-3 (-) decorate cell surface proteoglycans on activated stem/progenitor cells and appear to identify these cells in transitional areas of tissue development and in tissue repair and may be applicable to determining a more precise role for stem cells in tissue morphogenesis. Abstract : Surface regions of hip and knee rudiment cartilage from a 14 week gestational age human fetal specimen with stem cell niches delineated by immunolocalization of perlecan around these (top two images). Confocal images of knee rudiment tibial cartilage depict progenitor cells expressing the 4C3 and 7D4 sulfation motifs. Cell nuclei are stained red with propidium iodide.